A coastal vegetation survey of Pahang , Malaysia - Rozainah, M.Z. (Universiti Kebangsaan Malaysia, 2006)
A survey on coastal vegetation of Pahang in some localities from Sg. Balok in Kuantan southwards to Kuala Endau in Rompin was conducted from middle 2004 to early 2005. A total of 88 species of plants were recorded and identified mostly to the generic or species level. The usual vegetation types were sand and mudflat beach vegetations like Pandanus odoratissimus, Ipomoea pes capre and Casuarina equisetifolia and mangrove vegetation like Sonneratia caseolaris, Rhizophora mucronata and Avicennia marina. This paper also reports some unique heath-type forest vegetation like Hopea spp. in Menchali area.